The secret life of pets 2 - Renaud, Chris; Ford, Harrison, 1942-; Oswalt, Patton, 1969-; Hart, Kevin, 1979-; Universal Studios Canada (Willowdale, Ontario Universal Studios Canada, 2019)
Terrier Max is coping with some major life changes. His owner is now married and has a toddler, Liam. Max is so worried about protecting the boy that he develops a nervous tic. On a family trip to a farm, Max and Duke encounter many creatures who elevates Maxb2ss anxiety. Luckily, Max gets some guidance from veteran farm dog Rooster, who pushes Max to ditch his neuroses, find his inner alpha, and give Liam a little more freedom. Can Max and the gang find the courage to face their biggest fears?
Title from web page.
Originally released as a motion picture in 2019.
Wide screen.
Patton Oswalt, Kevin Hart, Harrison Ford.
Rating: PG; for some action and rude humor.
DVD, wide screen presentation.
Keywords: Pets -- Juvenile films; Pets -- Drama; Manhattan (New York, N.Y.) -- Juvenile films; New York (State) -- New York -- Manhattan; DVD-Video discs; Children's films; Action and adventure films; Animated films